Mobilization of epithelial mesenchymal transition genes distinguishes active from inactive lesional tissue in patients with ulcerative colitis. (1st June 2015) - Zhao, Xinmei; Fan, Jinshui; Zhi, Fachao; Li, Aimin; Li, Chen; Berger, Alan E.; Boorgula, Meher Preethi; Barkataki, Sangjucta; Courneya, Jean-Paul; Chen, Yuqing; Barnes, Kathleen C.; Cheadle, Chris
Abstract : Ulcerative colitis (UC) is a chronic, relapsing and debilitating idiopathic inflammation, with variable and complex pathophysiologies. Our objective was to elucidate patterns of gene expression underlying the progression of UC disease. Single endoscopic pinch FFPE biopsies ( n = 41) were sampled at both active and inactive stages at the same site in individual UC patients and compared with each other and with non-inflammatory bowel disease healthy controls. Gene expression results were validated by quantitative reverse transcriptase-PCR (QRT-PCR), and results at the protein level were validated by immunohistochemistry and western blot. Analysis of microarray results demonstrated that UC patients in remission display an intermediate gene expression phenotype between active UC patients and controls. It is clear that UC active site recovery does not revert fully back to a healthy control phenotype. Both UC active and inactive tissue displayed evidence, at both the gene expression and protein level, of a positive precancerous state as indicated by increases in the expression of Chitinase 3-Like-1, and the colorectal cancer metastasis marker MMP1. A key distinguishing feature between active and inactive UC, however, was the mobilization of marker genes and proteins for the Epithelial Mesenchymal Transition (EMT) pathway only in active UC. Analysis of the gene expression signatures associated with UC remission identified multiple pathways which appear to be permanently dysregulated in UC patients at formerly active sites in spite of clear histological recovery. Among these pathways, the EMT pathway was specifically up-regulated only in active UC emphasizing the potential for cancer progression in these patients.